UPAYA PENINGKATAN PRODUKTIVITAS PADI SAWAH MELALUI PENDEKATAN PENGELOLAAN TANAMAN DAN SUMBERDAYA TERPADU - Fitri Mahyudi (Fakultas Pertanian UVAYA Banjarmasin, 2020)
The objective of this assessment was to test of Integrated Crop Management (ICM) on irrigated rice implementtation model. The assesment was conducted in two locations, namely Sungai Tabuk district and Gambut district. The research activity begin from the second planting season 2011 , with the number of farmers cooperator with on Farm Adaptive Research approach. Result of theassesment showed that; (a) the implementation of ICM model with components technology (seed treatment, planting young rice seedling and single seedling per hill, application organic matter, application nitrogen fertilizer based on Leaf Color Chart reading, application of P dan K fertilizer base, employment of mechanical weeder on irrigated rice can increase of rice yield.